Coronary heart disease and stroke disease burden attributable to fruit and vegetable intake in Japan: projected DALYS to 2060 - Xiuting Mo; Ruoyan Tobe Gai; Kimi Sawada; Yoshimutsu Takahashi; Sharon E. Cox; Takeo Nakayama; Rintaro Mori (BMC, 2019)
Abstract Background Fruit and vegetable consumption was considered a protective effect against cardiovascular and cerebrovascular diseases (CVDs). This study aimed to project the reduction in the CVD burden under different scenarios of increased fruit and vegetable intake in Japan by 2060. Methods Population attributable fractions (PAF) were calculated by gender and age in 2015. The projection considered five scenarios for 2015, 2030, 2045, and 2060: 1) a baseline of no changes in intake; 2) a moderate increase in fruit intake (extra 50 g/day or 1/2 serving); 3) an high increase in fruit intake (extra 100 g/day or 1 serving); 4) a moderate increase in vegetable intake (extra 70 g/day or 1 serving); and 5) an high increase in vegetable intake (extra 140 g/day or 2 servings). Potentially preventable disability-adjusted life years (DALYs) for CVDs were estimated for each scenario. Monte Carlo simulations were performed to calculate the 95% confidence intervals of the estimates. Results Across all age groups, men had a higher daily vegetable intake than women (292.7 g/d > 279.3 g/d) but a lower daily fruit intake (99.3 g/d < 121.0 g/d). Comparing with recommended intake level (350 g/d of vegetable and 200 g/d of fruit), the total CVD burden was estimated to be 302,055 DALYs attributable to inadequate fruit consumption in 2015, which accounted for 12.6% of the total CVD burden (vegetable: 202,651 DALYs; 8.5%). In 2060, the percentage of the CVD burden due to insufficient intake of fruit is estimated to decrease to 7.9% under the moderate increase scenario and to decrease to 4.5% under the high increase scenario (vegetable: 5.4%; 2.4%). Conclusions The study suggested that a relevantly large percentage of the CVD burden can be alleviated by promoting even modest increases in fruit and vegetable consumption in Japan.